A Novel Promising Endometrial Preparation Protocol for Frozen-Thawed Embryo Transfer: A Randomized Controlled Trial - Li, Jian-Chun; Wang, Yan-Hong; Peng, li-Ying; Zhou, Yun; Chao, Shi-Bin (Frontiers in Endocrinology, 2021)
Background In recent years frozen-thawed embryo transfer (FET) has played an increasingly important role in ART, but there is limited consensus on the most effective method of endometrial preparation (EP) for FET. Inspired by significantly higher implantation rate and clinical pregnancy rate of the depot GnRH-a protocol, we proposed a novel EP protocol named down-regulation ovulation-induction (DROI) aimed to improve pregnancy outcomes of FET. Methods This was a single-center, randomized controlled pilot trial. A total of 307 patients with freeze-all strategy scheduled for first FET were enrolled in the study. A total 261 embryos were transferred in DROI-FET group including 156 patients and 266 embryos were transferred in mNC-FET group including 151 patients. Reproductive outcomes were compared between the two groups. Results The basic characteristics of patients, and the average number, quality and stage of embryos transferred were comparable between the two groups. Our primary outcome, implantation rate(IR) in DROI-FET group, was significantly higher than that of the mNC-FET group (54.41% versus 35.71%, P<0.01). The clinical pregnancy rate (CPR) and ongoing pregnancy rate (OPR) in DROI-FET group was also higher than that in mNC-FET group (69.87% versus 50.33%, P<0.01; 64.10% versus 42.38%, P<0.01). Conclusion(s) Compared to existing endometrial preparation methods, the DROI protocol might be the more efficient and promising protocol.